Seeded growth of gold-based nanoscale homojunctions via controlled etching regrowth and their applications for methanol oxidation reaction. Issue 4 (5th January 2023) - Wu, Quansen; Zhang, Gongguo; Wang, Yingying; Jiao, Yaqi; Ma, Yanyun; Zheng, Yiqun
Abstract : Gold-based nanoscale homojunctions are prepared via seeded growth mediated with controlled etching regrowth, exhibiting improved electrochemical activity for MOR. Abstract : We report a niche route to the fabrication of Au-based hybrid nanostructures in the form of homojunction via seeded growth mediated with etching regrowth. In particular, the trioctahedral Au nanoparticles are initially doped with limited amounts of Pt/Ag atoms on the surface, followed by oxidative etching using HAuCl4 . Instead of truncation on sharp corners/edges, the resulting products maintain the trioctahedral morphology but with an extra segment anchored on one side of the particle. Due to the structural advantages in metal–metal interface engineering and elemental doping, the current Au-based nanoscale homojunctions exhibit improved specific activity, reaction kinetics, and long-term durability in electrooxidation of methanol, as compared to pure Au trioctahedral counterparts. As verified by DFT simulation, such high catalytic performance can be ascribed to the favorable adsorption of the reactive species and low energy barrier for the rate determining step of Pt/Ag doping on the Au-Au interface. The present study introduces a niche synthetic strategy to create noble metal hybrid nanostructures based on oxidative etching and validates their promising use in electrocatalysis, which could be beneficial for the rational design of advanced fuel cell catalysts with versatile interface engineering.